2017
DOI: 10.1016/j.ygyno.2017.01.015
|View full text |Cite|
|
Sign up to set email alerts
|

Single cell sequencing reveals heterogeneity within ovarian cancer epithelium and cancer associated stromal cells

Abstract: Objectives The purpose of this study was to determine the level of heterogeneity in high grade serous ovarian cancer (HGSOC) by analyzing RNA expression in single epithelial and cancer associated stromal cells. In addition, we explored the possibility of identifying subgroups based on pathway activation and pre-defined signatures from cancer stem cells and chemo-resistant cells. Methods A fresh, HGSOC tumor specimen derived from ovary was enzymatically digested and depleted of immune infiltrating cells. RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 35 publications
(44 reference statements)
5
73
2
Order By: Relevance
“…A recent study utilised the single‐cell RNA sequencing approach to profile one single HGSOC tumour sample and identified two distinct cell populations. Both an epithelial cell population and a separate mesenchymal, stem cell‐like population were identified, reaffirming the prevalence of ITH in OC .…”
Section: Introductionmentioning
confidence: 53%
“…A recent study utilised the single‐cell RNA sequencing approach to profile one single HGSOC tumour sample and identified two distinct cell populations. Both an epithelial cell population and a separate mesenchymal, stem cell‐like population were identified, reaffirming the prevalence of ITH in OC .…”
Section: Introductionmentioning
confidence: 53%
“…CAFs, potentially originating from various types of cells, appear in all stages of cancer and have pivotal roles in creating tumor microenvironments . As it relates to OvCa, a variety of CAFs have been reported to comprise the tumor stroma, thereby contributing to the development of stromal heterogeneity . Moreover, it has been recognized that mesenchymal conversion of MCs is associated with tissue fibrosis in peritoneal dialysis .…”
Section: Discussionmentioning
confidence: 99%
“…25 As it relates to OvCa, a variety of CAFs have been reported to comprise the tumor stroma, thereby contributing to the development of stromal heterogeneity. 43,44 Moreover, it has been recognized that mesenchymal conversion of MCs is associated with tissue fibrosis in peritoneal dialysis. 45,46 It has also been proposed that the transition of mesothelial cells, predominantly initiated by TGF-β1, has an important role in the development of peritoneal metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…New experimental techniques provide the opportunity to interrogate such hypotheses directly. This phenomenon has been observed in 66 single cells in a HGSC tumor [87] and a subset of glioblastoma tumors by single cell profiling [88]. However, it has been recently shown that glioblastoma tumors are inherently heterogeneous by chance [89], and more single cell data is required to fully explore this phenomenon.…”
Section: Characteristics Of Hgsc Molecular Subtypesmentioning
confidence: 94%